THE CONFLICT IN SOUTH OSSETIA AND THE FRONTIERS OF STRUGGLE FOR THE GREATER CASPIAN’S ENERGY RESOURCES - MAGOMEDOV, Arbakhan (CENTRAL ASIA AND THE CAUCASUS, 2009)
The oil pipeline projects overshadowed the conflict in South Ossetia from its very beginning. The TV audience was especially impressed by the picture of the Azpetrol tank cars burning somewhere in Georgia. The Caspian oil market promptly responded to the warfare: British Petroleum, the BTC operator, suspended oil pumping along this route; the same was done on the Baku-Supsa pipeline; and the Poti and Kulevi oil terminals were left idling.Later numerous surveys and analyses stressed the economic aspects and calculated the losses sustained by Azerbaijan and the Western oil companies. It seems that the political analysts were more concerned about how much the war cost Azerbaijan and British Petroleum in lost profit and how many million tons of oil did not reach the market than about anything else. As Azerbaijan and the BTC shareholders regained their lost profits, the issue gradually retreated into the background. This left the geopolitical effect of the events in the shadow. From the very beginning, however, the South Ossetian conflict had obvious global implications. In his article “La Lezione di Putin alla Casa Bianca,” Lucio Caracciolo wrote: “The Georgian war not merely produced a colossal regional effect; it is helping to revise the global balance which, it seems, was firmly established late last century.”1Few of the analysts, however, tried to answer the question of whether the sides’ geopolitical interests can be discerned in the figures of the losses and profits of those involved in the Caspian oil business. A positive answer suggests the question: What are these interests? Seen from this angle, the causes, both obvious and concealed, of the August war and the key stimuli this inspired in the sides become much clearer.Here I intend to reveal the nature of the geopolitical race for the energy and transportation resources of the Greater Caspian2 at all stages of its post-Soviet development and concentrate on the rapidly accelerating rivalry in the 21st century with its unexpected, yet logical, post-Tskhinvali finale.